Delayed HIV diagnosis during the COVID‐19 pandemic in Poland: A call for targeted HIV testing for those under suspicion of SARS‐CoV‐2. Issue 11 (13th November 2022) - Suchacz, Magdalena M.; Krankowska, Dagny; Cybula, Aneta; Kamerys, Juliusz; Jabłonowska, Elżbieta; Rozpłochowski, Błażej; Bociąga‐Jasik, Monika; Wiercińska‐Drapało, Alicja
Abstract: Objectives: The aim of this study was to analyse patients newly diagnosed with HIV who were originally admitted to hospitals with suspicion of COVID‐19. Methods: This was a retrospective case series undertaken at four sites. Only adults with new HIV diagnosis and COVID‐19 exclusion hospitalized in 2020–2021 were included. Demographic, clinical and laboratory data were collected from medical records. Results: Twenty‐five patients were included in the analysis: 19 men (76%), 11 of Ukrainian origin (44%). The median age was 38.5 years (range 25–59). The mode of HIV transmission was heterosexual for 11 (44%) patients, eight (32%) were men who have sex with men and three (12%) were people who inject drugs. The median duration of symptoms prior to hospital presentation was 20.6 days (range 3–90). The median number of SARS‐CoV‐2 tests per patient was 2.62 (range 1–7). All SARS‐CoV‐2 tests were negative. Screening for HIV was performed on average on the 18th day of hospitalization (range 1–36 days). Twenty‐three patients (92%) were late presenters, 22 (88%) had advanced disease, and 19 (76%) were in the AIDS stage. The median CD4 T‐cell count was 72 cells/μL (range 3–382). The rate of positive HIV testing at the two sites where it was available for people with suspected COVID‐19 was 0.13% (7/5458 during the study period). Conclusions: We strongly recommend introducing the HIV screening test in the diagnostic algorithm for every patient suspected of having COVID‐19, presenting with clinical and/or radiological pulmonary symptoms.